Numerical simulation of the supercritical electron beam dynamics in magnetic field of finite size in the presence of plasma - Markov, P.I.; Onishchenko, I.N.; Sotnikov, G.V. (Вопросы атомной науки и техники, 2004)
The first results of development of a numerical electromagnetic 2.5-dimensional code «SOM 2.5» (3 dimensional by the velocities and 2 dimensional by the coordinates) for researching of a virtual cathode in the presence of
plasma are submitted. Представлено перші результати створення чисельного електромагнітного 2,5-мірного (3-х мірного по
швидкостях і 2-х мірного по координатах) коду для дослідження віртуального катоду в присутності плазми. Представлены первые результаты создания численного электромагнитного 2,5-мерного (3-х мерного по
скоростям и 2-х мерного по координатам) кода для исследования виртуального катода в присутствии плазмы.